Are the IR cameras FLIR ONE suitable for clinical applications? - Ricardo Vardasca, PhD, ASIS, FRPS (2019)
BACKGROUND: Infrared Thermography (IRT) has been used in clinical environments for at least six decades. In 2014 affordable and attractive low-cost infrared cameras were introduced into the market that facilitated the ability of being at- tached to mobile devices such as tablets and smartphones. Despite these cameras do not satisfy the minimum specifica- tions recommended for clinical use they have already been used in clinical applications. It is therefore important to verify the performance of these devices. In this paper the start-up stability and the absolute temperature offset, in particular within the temperature range of the human body, are evaluated using the android and iOS OEM connection versions of the FLIR ONE IR 2nd generation and compared from the end user point of view. MATERIALS AND METHODS: Four FLIR ONE IR 2nd generation cameras were used, two developed to be attached to android systems and the other two to apple iOS systems. A start-up drift test at 30 ºC and a temperature sweep from 20 ºC to 40 ºC in steps of 1 ºC, representing the human body temperature range, were carried out. For the temperature perfor- mance assessments, a blackbody Isotech Hyperion R Model 982 was used as temperature reference (uncertainty of ±0.1°C). It was first set at 30ºC temperature reference for the start-up drift test, the cameras along with the attached de- vices were switched on and measurements were taken at five-minute intervals for one hour at a distance of 30 cm from the blackbody target. For the temperature sweep, the blackbody reference was set to 20ºC. Images were then taken with the IRT imaging devices and readings were taken while the blackbody setpoint was increased in steps of 1ºC up to 40ºC, wait- ing 15 minutes in between each step for blackbody temperature stability. RESULTS: The FLIR One 2nd generation thermal cameras overestimate the temperature reading during the start-up off set drift test and take around 15 to 20 minutes to reach measurement stability with an average difference from the blackbody indicated temperature of 0.9 ºC. In the human body temperature offset drift test there is a higher difference from the calibration source at temperatures below 24 ºC, where the temperature readouts are more than 2.0 °C above the real temperatures set at the blackbody. There is a high interclass correlation between the thermal cameras' readings and the calibration source set temperatures and also between the measurements of the two OEM versions of the thermal cam eras studied. The span of limits of agreement (LOA) of the measurements of all FLIR ONE 2nd generation cameras with the blackbody temperature was 2.23 ºC. CONCLUSIONS: Despite these systems being attractive in price and manufacturer provided features, their operational performance does not comply with the required standards for clinical use. The thermal information provided by these im aging systems should only be taken into account for monitoring purposes, as some previous research demonstrated, and not as an input for diagnostic judgments, if they require absolute temperature values to be correct. It is important to note that the cameras provider does not advertise them as medical devices.